2023
DOI: 10.3390/tropicalmed8050243
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Profile: A European Multidisciplinary Network for the Fight against HIV Drug Resistance (EuResist Network)

Abstract: The EuResist cohort was established in 2006 with the purpose of developing a clinical decision-support tool predicting the most effective antiretroviral therapy (ART) for persons living with HIV (PLWH), based on their clinical and virological data. Further to continuous extensive data collection from several European countries, the EuResist cohort later widened its activity to the more general area of antiretroviral treatment resistance with a focus on virus evolution. The EuResist cohort has retrospectively e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The detection of SDRMs in the present study was consistent with other recent studies published in Europe [ 6 , 7 , 8 ], making our findings one of the more up-to-date studies including the surveillance of resistance to INSTIs. The rate of SDRMs conferring resistance to NRTIs remained stable and similar to a previous study conducted in Portugal [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The detection of SDRMs in the present study was consistent with other recent studies published in Europe [ 6 , 7 , 8 ], making our findings one of the more up-to-date studies including the surveillance of resistance to INSTIs. The rate of SDRMs conferring resistance to NRTIs remained stable and similar to a previous study conducted in Portugal [ 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…Upon identification of a DRM, ART regimens are usually modified accordingly, replacing ineffective drugs with those that are expected to effectively suppress the viral replication [ 5 ]. The European multi-center cohort study conducted in the past 10 years and the Portuguese HIV drug resistance (HIVDR) study conducted in 2021 showed that the prevalence of HIV resistance increased over time [ 6 , 7 , 8 ]. Based on this evidence, the World Health Organization (WHO) stated that further investigation on this subject is necessary in this era of a global scale-up of ART to achieve the 95-95-95 targets [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Euresist Integrated Database EIDB is one of the world’s largest databases regarding drug resistance in HIV-infected patients, both treatment-naïve and treated, undergoing clinical follow-up since 1998 ( Rossetti et al 2023 ). The data comprises nine national cohorts from Italy, Germany, Sweden, Portugal, Spain, Luxembourg, Belgium, Turkey, and Russia.…”
Section: Experiments and Resultsmentioning
confidence: 99%